Analysis of the Royal Pita Maha Ubud Management Strategy in Improving the Competitiveness of Tourism Accommodation: Supporting Factors and Obstacles to Development - Anak Agung Istri Wahyu Bira Dewi dewi; I Gusti Made Widya Sena; I Nyoman Piartha (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the management strategy of The Royal Pita Maha Resort using the POAC (Planning, Organizing, Actuating, Controlling) approach and a SWOT analysis to understand the strengths, weaknesses, opportunities, and threats in developing a culture-based and sustainable resort. The method used is qualitative research with interviews, observation, and documentation as the main data sources. The results show that the management strategy has been running well through local culture-based planning, a clear organizational structure, the implementation of premium services, and regular quality monitoring. The SWOT analysis shows that significant opportunities lie in the trends of sustainable tourism, wellness tourism, and the upper-middle-class domestic market. However, the resort also faces threats such as competition from luxury accommodations, changing tourist preferences, and dependence on international tourists. Overall, The Royal Pita Maha Resort is strategically positioned to grow through continuous innovation and adaptation.